Action Research for Exploring Genre Approaches to Writing in Real-World ESP Classrooms - Uma Maheswari Rajagopalan; Lynda Griffin; Paola Trimarco (International Journal of Education, 2024)
This paper investigates how action research can be used to develop genre-approaches to teaching using a case study of teaching research article (RA) abstract writing on a course in Japan for science and technology students. This study involved two pedagogies placed within genre-awareness approaches, with moves being taught at different stages for each classroom. In addition to the teacher’s observations and a questionnaire to evaluate students’ perceptions, written drafts from both groups were analysed at two stages. Our analysis reveals that earlier intervention in teaching moves helped students to better construct their abstracts and that language-based activities played a role in improving students’ abstract writing without moves-based instruction. Moreover, the exercise of conducting this study in an action research framework highlighted the advantages of using a cyclic framework which allows for timely intervention based on teacher observation and critical evaluation of the teaching and learning context as the task progresses.